Ultrasonic speeds, refractive indices, and densities of dimethoxymethane plus aliphatic alcohols (C-1-C-4) at (298.15 and 303.15) K with COSMO-RS and ERAS analyses - Yau, C.K.; Nabi, F.; Jesudason, C.G. (2015)
The ultrasonic speeds, refractive indices, and densities of binary mixtures dimethoxymethane + aliphatic alcohols (C-1-C-4) were determined. The excess quantities for the binary mixtures are fitted to the Redlich-Kister polynomials. The observed excess molar volumes are rationalized in terms of the intermolecular force and geometry contributions of the constituent molecules. The intermolecular forces are discussed using accepted theories and the more recent conductor-like screening model (COSMO). The extended real associating solution (ERAS) model is also utilized in the analysis of excess molar volumes. The a-profile of dimethoxymethane and alcohols are computed with COSMO-RS and interpreted to be not supportive of earlier interpretations of hydrogen bonds in the energetics. Sign changes in excess molar volume and excess isentropic compressibility are discussed and rationalized in detail quantitatively. Sellmeier's equation is used to quantitatively rationalize the measured refractive indices and a consistency with regard to sign and sign changes of the other measured excess quantities can be deduced. (C) 2015 Elsevier B.V. All rights reserved.